2010
DOI: 10.1016/j.clim.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered cytokine production by dendritic cells from infants with atopic dermatitis

Abstract: Dendritic cells (DC) are potent initiators of immune responses, compared to other professional antigen-presenting cells, based on their ability to capture antigen, express high amounts of MHC and co-stimulatory molecules, and to secrete immunostimulatory cytokines. Altered functions of DC in atopic individuals have been observed, though it is not clear if this is a cause or a result of the development of allergic disease. In this report we demonstrate altered cytokine production by DC isolated from infants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We have previously established that there are systemic effects of Stat6VT Tg expression in T cells (810). Indeed, we previously observed that dendritic cells in neonatal mice from Stat6VT Tg dams exhibited altered cytokine production that was similar to patterns observed in infants from atopic mothers (5,31). This suggests that although FucT-VII deficiency is protective for allergic skin inflammation in the absence of additional proatopic signals, the effects of an atopic environment on the infants immune system can overcome that protection.…”
Section: Discussionsupporting
confidence: 52%
“…We have previously established that there are systemic effects of Stat6VT Tg expression in T cells (810). Indeed, we previously observed that dendritic cells in neonatal mice from Stat6VT Tg dams exhibited altered cytokine production that was similar to patterns observed in infants from atopic mothers (5,31). This suggests that although FucT-VII deficiency is protective for allergic skin inflammation in the absence of additional proatopic signals, the effects of an atopic environment on the infants immune system can overcome that protection.…”
Section: Discussionsupporting
confidence: 52%
“…Supporting this notion is a recent study that reported that several specific conditions can stimulate innate immune system (like toll-like receptor 4) that this induces TSLP expression [28,29,30]. Metabolic changes (including ROS generation) in the local milieu may program innate immune system at the site of inflammation to produce Type 2 responses [28,31].…”
Section: Discussionmentioning
confidence: 73%
“…A prior study demonstrated elevated IL-6 production by T cells derived from patients with AD ( 72 ). Additionally, IL-6 is generated by various cell types, including dendritic cells, mast cells, eosinophils, and keratinocytes ( 73 76 ). After the application of MC903 in Fut1- KO mice, there was a significantly elevated production of IL-6 in the skin, along with increased infiltration of mast cells and eosinophils compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%